DEPICTING THE MOROCCAN MUSLIM WOMAN'S STRUGGLE AGAINST THE PATRIARCHAL AFRICAN-MUSLIM CONTEXT IN THE POSTCOLONIAL MOROCCO - El Aissi, Hanane; Muflichah, Siti (Khazanah: Jurnal Studi Islam dan Humaniora, 2023)
This essay aims to show how much Leila Abouzeid, the author of the novel Year of Elephant, has developed her own discursive space in order to express the unspoken and depict the abrupt trauma of postcolonial Morocco from a postcolonial feminist perspective. The concept of "the Future" or "l'Avenir" of Jacques Derrida should unquestionably be implied in the aftermath of postcolonial Morocco. In this setting, Morocco's post-colonial fallout is obvious and predictable. The marriage, education, and administrative institutions have all been severely corrupted. Women who gave their lives in the armed resistance are now abruptly subject to patriarchy, mistreated by customs, and shunned by the law. Through qualitative description, this paper claims that the experiences of women in colonialism are celebrated. Using feminist research, experiences of women from postcolonial Morocco have been voiced and the novel portrays a woman’s spiritual journey, and it is an event of cross-cultural literary history. Published in 1989, Year of the Elephant has had a great impact on promoting Moroccan women’s legal situation in contemporary Morocco. The new millennium has signaled a new phase for women’s legal triumph.